2018
DOI: 10.1002/jsfa.9056
|View full text |Cite
|
Sign up to set email alerts
|

Urea plus nitrate pretreatment of rice and wheat straws enhances degradation and reduces methane production inin vitroruminal culture

Abstract: Urea+nitrate pretreatment combines positive effects of urea pretreatment and nitrate supplementation, and can be a potential strategy to improve ruminal biodegradation, facilitate propionate production and reduce methane production from lignified straws. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…It has been reported that UN pretreatment improved ruminal degradation of rice straw measured in in vitro batch incubation [9]. The present in vivo study also indicates that goats fed UN had greater total-tract digestibility of NDF than those fed control.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It has been reported that UN pretreatment improved ruminal degradation of rice straw measured in in vitro batch incubation [9]. The present in vivo study also indicates that goats fed UN had greater total-tract digestibility of NDF than those fed control.…”
Section: Discussionsupporting
confidence: 75%
“…A shortage of [H] would result in reduced methanogenesis. Our previous in vitro study found that urea plus nitrate pretreatment for rice straw decreased CH 4 production with a reduction of acetate to propionate ratio [9]. van Zijderveld et al [38] observed that nitrate supplementation caused CH 4 inhibition, which was accompanied by increased propionate molar proportion at the expense of acetate and butyrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, inclusion of high level of concentrate in the diet represents higher content of readily fermentable substance (e.g., starch) than that of high forage diets. Previous studies demonstrated that starch-rich diets reduced ruminal pH and H 2 concentration, and shifted fermentation patter towards to an increased propionate formation, which would depress the activity of methanogens and consequently reduce CH 4 emissions [30,31]. Moreover, the composition and structure of ruminal methanogens was demonstrated to differ across heifer physiological stages, which would affect the enteric CH 4 emissions of heifers [32].…”
Section: Discussionmentioning
confidence: 99%